Emerging Role of Precision Medicine in Diagnosis and Treatment of Chronic Respiratory Disease - Wesnawa, Made Agustya Darma Putra; Asmara, Oke Dimas; Supadmanaba, I Gede Putu (Faculty of Medicine Universitas Airlangga, 2024)
Precision medicine is the current approach to managing chronic respiratory diseases, especially asthma and chronic obstructive pulmonary disease (COPD). It involves the evaluation of genetic, environmental, and lifestyle variations for each patient. It requires valid and specific biomarkers obtained through genetic studies, biomolecular technology, and omics-based technology to determine targeted therapies. Asthma and COPD have heterogeneous clinical phenotype variations, and giving one standard treatment for asthma and COPD may not necessarily provide the same effectiveness to other patients. The endotype, a specific molecular mechanism in disease pathogenesis, is essential in phenotype variation. The role of precision medicine in asthma and COPD is to determine endotypes through specific biomarkers and to provide specific targeted therapy for achieving personalized treatment in each patient. The application of precision medicine not only provides precise diagnosis and treatment but also enables early detection in individuals at risk and prevention of progression and exacerbation in asthma and COPD.